Thermal properties of the orthorhombic CaSnO3 perovskite under pressure from ab initio quasi-harmonic calculations - Maul, J. [UNESP]; Santos, I. M.G.; Sambrano, J. R. [UNESP]; Erba, A. (Springer Nature, 2016)
Structural, elastic and thermodynamic properties of the orthorhombic CaSnO3 perovskite are theoretically investigated at the ab initio level as a function of temperature and pressure. Harmonic and quasi-harmonic lattice dynamical calculations are performed with the Crystal program, by explicitly accounting for thermal expansion effects and by exploring the effect of several DFT functionals. The anisotropic, directional elastic response of the system is characterized up to 20 GPa of pressure. The thermal lattice expansion and elastic bulk modulus are described at simultaneous temperatures up to 2000 K and pressures up to 20 GPa. The Gibbs free energy of formation of CaSnO3 from CaO and SnO2 as a function of temperature is also addressed by means of fully converged phonon dispersion calculations on the three systems.
Keywords: CaSnO; CRYSTAL program; Perovskite; Pressure–temperature; Quasi-harmonic